Literature Review on the Influence of Leadership Style on Employee Satisfaction and Performance - Firayani Firayani (Oikonomia : Journal of Management Economics and Accounting, 2024)
This study aims to analyze the influence of leadership styles on employee satisfaction and performance through a literature review approach. Using a descriptive qualitative method, this study collected and reviewed various relevant academic literature published in the last five years. The primary focus was on identifying leadership styles such as transformational, transactional, authoritarian, and democratic, and their relationship to job satisfaction and individual performance variables within an organizational context. The analysis results indicate that transformational and democratic leadership styles have the most positive influence on improving employee satisfaction and performance. Conversely, authoritarian and transactional leadership styles tend to have limited and contextual impacts. Job satisfaction proved to be an important intermediary variable in bridging the influence of leadership styles on performance. These findings emphasize the importance of leaders adopting a leadership approach that is adaptive, communicative, and oriented toward developing interpersonal relationships. This research also provides conceptual contributions to organizations in designing more effective and humanistic leadership strategies. Overall, this study enriches the human resource management literature and offers a theoretical basis for further research.